INTERTEXTUALITY ACROSS MEDIA: THE NARRATIVE TRANSFORMATION OF “KKN DI DESA PENARI” FROM TWEET TO MOTION PICTURE AND DIGITAL POP CULTURE - Riyanto, Ina Listyani; Sunarmi, Sunarmi; Ajidarma, Seno Gumira (jfpublisher, 2025)
This study investigates the narrative transformation of KKN di Desa Penari as it migrated across multiple media platforms, illustrating how local stories are reinterpreted within Indonesia’s hybrid digital ecosystem. Originating as a Twitter thread, the narrative evolved into novels, films, and user-generated content, reflecting the dynamic interplay between intertextuality, adaptation, remediation, and participatory culture. While previous studies have addressed digital folklore or single-medium adaptations, few have explored how a single narrative transforms holistically across platforms through both formal production and audience engagement. The purpose of this study was to analyze how KKN di Desa Penari was reshaped through cross-platform adaptation, cultural negotiation, and participatory practices. Employing a descriptive qualitative approach with intertextual analysis, the research drew data from primary sources (Twitter thread, novel, film, memes, fan art, TikTok videos, YouTube commentary) and secondary literature. The findings reveal that each medium reconfigured the narrative in distinct ways: Twitter fostered fragmented, speculative storytelling; the novel embedded local moral codes; the film remediated the story into visual spectacle; and user-generated content extended the narrative through reinterpretation and cultural commentary. This study contributes to understanding how local narratives achieve longevity and cultural relevance through digital convergence and audience co-creation.